A novel speech prosthesis for mandibular guidance therapy in hemimandibulectomy patient: A clinical report - Raghavendra Adaki; Kamal Shigli; Dinshaw M Hormuzdi; Sivaranjani Gali (Wolters Kluwer Medknow Publications, 2016)
Treating diverse maxillofacial patients poses a challenge to the maxillofacial prosthodontist. Rehabilitation of hemimandibulectomy patients must aim at restoring mastication and other functions such as intelligible speech, swallowing, and esthetics. Prosthetic methods such as palatal ramp and mandibular guiding flange reposition the deviated mandible. Such prosthesis can also be used to restore speech in case of patients with debilitating speech following surgical resection. This clinical report gives detail of a hemimandibulectomy patient provided with an interim removable dental speech prosthesis with composite resin flange for mandibular guidance therapy.